Overview of biofertilizers in crop production and stress management for sustainable agriculture - Chaudhary, Parul; Singh, Shivani; Chaudhary, Anuj; Sharma, Anita; Kumar, Govind (Frontiers in Plant Science, 2022)
The increase in world population, the demography of humans estimated to be exceeded and it has become a major challenge to provide an adequate amount of food, feed, and agricultural products majorly in developing countries. The use of chemical fertilizers causes the plant to grow efficiently and rapidly to meet the food demand. The drawback of using a higher quantity of chemical or synthetic fertilizers is environmental pollution, persistent changes in the soil ecology, physiochemical composition, decreasing agricultural productivity and causes several health hazards. Climatic factors are responsible for enhancing abiotic stress on crops, resulting in reduced agricultural productivity. There are various types of abiotic and biotic stress factors like soil salinity, drought, wind, improper temperature, heavy metals, waterlogging, and different weeds and phytopathogens like bacteria, viruses, fungi and nematodes which attack on plants, reduced crop productivity and quality. There is a shift towards the use of biofertilizers due to all these facts, which provide nutrition through natural processes like zinc, potassium and phosphorus solubilization, nitrogen-fixation, production of hormones, siderophore, various hydrolytic enzymes; protect the plant from different plant pathogens and stress conditions. They provide the nutrition inadequate amount that is sufficient for healthy crop development to fulfill the demand of the increasing population worldwide, eco-friendly and economically convenient. This review will focus on biofertilizers and their mechanisms of action, role in crop productivity and in biotic/abiotic stress tolerance.